Adaptive Control Over the Permanent Characteristics of a Wind Turbine. (2015) - Solomin, E.V.; Sirotkin, E.A.; Martyanov, A.S.
Abstract: Herein is proposed a system for adaptive speed control of the permanent characteristics of a wind turbine to ensure safe operation thereof. The design of wind turbines is generally calculated with the nominal power generation at a wind speed of 11 m/s, and it should be controlled at higher wind flow velocities. Rotation speed is the main control parameter of wind turbine system. In addition, the control system can provide normalized thermal conditions for the alternator and prevents exceeding vibration level. Adaptive control system contains mechanical and electromechanical modules intended for braking rotor using friction components. There is also a structure diagram of control system and transfer functions of system components.